2012
DOI: 10.1155/2012/628352
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Fatigue as an Indicator of Eccentric Exercise-Induced Muscle Injury: The Role of Vitamin E

Abstract: This study investigates whether vitamin E can attenuate eccentric exercise-induced soleus muscle injury as indicated by the amelioration of in situ isometric force decline following a low-frequency fatigue protocol (stimulation at 4 Hz for 5 min) and the ability of the muscle to recover 3 min after the termination of the fatigue protocol. Adult male Wistar rats were divided into vitamin E-supplemented or placebo-supplemented groups studied at rest, immediately post-exercise or 48 h post-exercise. Daily dl-α-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The major advantage of rats over mice is the greater tissue sample size and the larger blood volume that allows measurement of a complete set of blood biomarkers. Rats have been used to address diverse research questions in the exercise physiology field including physical performance (Veskoukis et al 2008;Booth and Laye 2009), metabolism (Nikolaidis et al 2004;Brooks 2009), fatigue (Allen et al 2008;Kyparos et al 2012), muscle atrophy (Fitts et al 2001;Kyparos et al 2005), gene expression, and signaling pathways (Nikolaidis et al 2003;R€ ockl et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The major advantage of rats over mice is the greater tissue sample size and the larger blood volume that allows measurement of a complete set of blood biomarkers. Rats have been used to address diverse research questions in the exercise physiology field including physical performance (Veskoukis et al 2008;Booth and Laye 2009), metabolism (Nikolaidis et al 2004;Brooks 2009), fatigue (Allen et al 2008;Kyparos et al 2012), muscle atrophy (Fitts et al 2001;Kyparos et al 2005), gene expression, and signaling pathways (Nikolaidis et al 2003;R€ ockl et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had demonstrated that temporary skeletal muscle injury can be induced in rats by horizontal treadmill exercise at a speed of 15-16 m/min for a cumulative period of approximately 90 min or until exhaustion. [23][24][25] Paola et al found that, in rats, horizontal treadmill exercise of 15-45 min per day for 2-4 weeks at a speed of 30-45 cm/s can accelerate functional recovery following traumatic muscular injury. 15,26 18 m/min for 5 min (rest interval 2 min and 18 times), can induce skeletal muscle injury and contraction excitation-coupling failure in rats.…”
Section: Discussionmentioning
confidence: 99%